Design of a novel co‐electrospinning system with flat spinneret for producing helical nanofibers. Issue 22 (26th October 2019) - Zhao, Tienan; Zheng, Yuansheng; Zeng, Yongchun
ABSTRACT: A kind of biomimetic fibers of helical structures at nanoscale has attracted increasing interest. In this study, a novel co‐electrospinning setup with a designed flat spinneret, used for the fabrication of helical nanofibers, is reported in this study. Poly( m ‐phenylene isophthalamide) (Nomex) and Thermoplastic polyurethane (TPU) are chosen as the two components in co‐electrospinning. To display the efficiency for producing helical fibers, a generally used core–shell needle spinneret is used for comparison. The effect of the uniformity of electric field distribution created by these two types of spinnerets on the jet motion and the resultant helical fibers is developed, with systematical simulation and experimental research. The results showed that the co‐electrospinning system with the newly designed flat spinneret can produce helical nanofibers efficiently. Compared with the needle spinneret, the flat spinneret created more uniform electric field, leading to better morphology and structure of the resultant helical fibers. In addition, an approach to achieve the scale‐up of this co‐electrospinning system is developed. This novel design is expected to provide a promising method to fabricate nanofiber materials with helical structures. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2019, 57, 1496–1505 Abstract : Helical nanofibers are fabricated by a novel co‐electrospinning system. The main innovation applied in this study is the designing of a flat spinneret, which allows for a more uniform electric field to be created. Consequently, helical nanofibers with better morphology are produced in comparison to those created in previous work.